Analisis Semiotika Nilai Perjuangan Seorang Ibu dalam Film “How to Make Millions Before Grandma Dies” - Ghassani, Aliesa Athirah; Khohar, Abdul; Romadlan, Said (Fakultas Ilmu Sosial dan Ilmu Poliitik Universitas Ichsan Gorontalo, 2025)
This research discusses the value of a mother's struggle in the movie ‘How to Make Millions Before Grandma Dies’. Film is a form of media in mass communication that has a big influence in conveying messages, stories and values ​​to its audience. The story of a mother's struggle is often a strong and inspiring theme, because the mother figure is usually the main pillar in the family and society. Especially in a family, the mother's role is very important. This research aims to describe the forms of a mother's struggle found in films ‘How to Make Millions Before Grandma Dies’. This research uses a qualitative approach with Ferdinand de Saussure's semiotic analysis method using observation and documentation techniques. The data analysis technique uses the theory of struggle by Joyomartono which includes 6 points of struggle values, namely: The value of being willing to sacrifice, unity, respect, patience, the spirit of never giving up and cooperation. The results of this research found 7 scenes of the value of struggle, with 2 scenes each of the value of sacrifice, 1 scene of the value of unity, 1 scene of the value of struggle, 1 scene of the value of patience, 1 scene of the value of never giving up and 1 scene of the value of cooperation. This study identified seven that depict the values of a mothr’s struggle, each highlighting aspect of sacrifice, resilience, and cooperation. These findings emphasize the significant role of visuals and dialogue in constructing narratives about women’s (mother’s) struggles, offering implications for gender analysis in media. Penelitian ini membahas tentang nilai perjuangan seorang Ibu pada film ‘How to Make Millions Before Grandma Dies’. Film merupakan salah satu bentuk media pada komunikasi massa yang memiliki pengaruh besar dalam menyampaikan pesan, cerita, dan nilai-nilai kepada penontonnya. Kisah perjuangan seorang Ibu sering kali menjadi tema yang kuat dan menginspirasi, karena sosok Ibu biasanya menjadi pilar utama dalam keluarga dan masyarakat. Terutama dalam sebuah keluarga, peran Ibu sangat penting. Penelitian ini bertujuan untuk mendeskripsikan bentuk-bentuk perjuangan seorang Ibu yang terdapat pada film ‘How to Make Millions Before Grandma Dies’. Penelitian ini menggunakan pendekatan kualitatif dengan metode analisis semiotika Ferdinand de Saussure dengan menggunakan teknik observasi dan dokumentasi. Teknik analisis data menggunakan teori perjuangan oleh Joyomartono yang mencakup sebanyak 6 poin nilai perjuangan yaitu: Nilai rela berkorban, persatuan, menghargai, sabar, semangat pantang menyerah dan kerja sama. Penelitian ini menemukan 7 adegan yang menggambarkan nilai perjuangan seorang Ibu. Dengan masing-masing mencakup pada pengorbanan, ketangguhan dan kerjasama. Hasil ini menegaskan peran penting pada visual dan dialog dalam membangun narasi pada perjuangan perempuan (Ibu) untuk memberikan implikasi pada analisis gender dalam media.